A Resilience and Robustness Oriented Design of Base-Isolated Structures: The New Camerino University Research Center - Dall’Asta, Andrea; Leoni, Graziano; Micozzi, Fabio; Gioiella, Laura; Ragni, Laura (Frontiers in Built Environment, 2020)
This paper analyses the new Research Centre designed for the University of Camerino and entirely financed by the national Civil Protection Department (DPC), following the seismic events in Central Italy in 2016. The building has been designed to guarantee speed of execution as well as a high level of safety, especially regarding seismic actions. The structural solution was to create an isolated system with a steel braced super-structure with pinned joints and r.c. sub-structures able to adapt to the complex morphology of the area. As described in the first part of the paper, design choices have been made to achieve a high level of resilience and robustness, i.e. to limit damage to structural and non-structural components and equipment under moderate and design seismic actions and to avoid disproportionate consequences in the event of extreme actions, larger than the design ones. In the second part of the paper, specific risk analyses have been carried out to evaluate the real performance of the building under increasing intensity levels, with reference to both serviceability and ultimate conditions. To this purpose a site-specific hazard study was first conducted, then nonlinear analyses were performed using a hazard-consistent set of records with return periods ranging from TR=60 years to TR=10000 years. The main demand parameters of both the isolation system and the super-structure were recorded and capacity values corresponding to different ultimate and damage limit conditions were defined. The results obtained in terms of demand hazard curves show that the building performances in terms of rustiness and resilience are very high, confirming the efficacy of the strategies adopted in the design.